Desain Program Pembelajaran Perspektif Keberagamaan Peserta Didik Sekolah Menengah Atas - Zainab, Khoirunnisa Shidqiyyah (Attractive : Innovative Education Journal, 2020)
Adolescence was a period in human life whose age and role limits are often not very clear. From such phenomena, one of the tools that can prevent the occurrence of adolescent problems, either self-inflicted, parents and society in general was a steady and steady Islamic religious education, as well as fostering a healthy and commendable personality. The purpose of this article was to analyze the students' religious development program that was a plan of activities, was used as a guide to make students able to practice their religious teachings well. This type of research was descriptive qualitative. Data analysis method was used by using descriptive methods. The results show that the implementation of religious programs in high school, seems to be more under the responsibility of the vice-principal of the student field, by looking at the data obtained, so many religious program activities to improve the quality of religious diversity of students in schools, either in the long term ( annual), monthly, weekly, and daily, which was a habituation activity. Keywords: Design of Learning Programs, Religious Programs